1988
DOI: 10.1111/j.1365-2621.1988.tb07704.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Freezing and Frozen Storage of Alaska Pollock on the Chemical and Gel‐Forming Properties of Surimi

Abstract: Alaska pollock was headed, gutted, and frozen at sea in pre-and postrigor condition. Surimi made from this fish held at -29°C showed a gradual loss in gel-forming ability with time of storage. This loss in gel-forming ability was accompanied by a loss in viscosity and Ca+ +-ATPase activity of the surimi over the g-month storage period. The gel strength of kamaboko gels showed an inverse linear relationship with gel moisture over a limited moisture range. Simply freezing and thawing pollock resulted in surimi w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 20 publications
1
31
1
Order By: Relevance
“…Washing removes compounds such as sarcoplasmic proteins, inorganic salts, low-molecular weight substances, lipids, and blood components (Benjakul et al 1998;DeWitt and Morrissey 2002), concentrating myofibrillar proteins, which play an essential role in gel formation, improving gel-forming ability and decreasing protein denaturation during frozen storage (Lee 1984;Lanier 1986;Scott et al 1988), and enhances color and flavor of products (Toyoda et al 1992). A substantial amount of muscle proteinases are also removed during the washing process in surimi production (Morrissey et al 1995;Benjakul et al 1998), resulting in less activity in surimi Benjakul et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Washing removes compounds such as sarcoplasmic proteins, inorganic salts, low-molecular weight substances, lipids, and blood components (Benjakul et al 1998;DeWitt and Morrissey 2002), concentrating myofibrillar proteins, which play an essential role in gel formation, improving gel-forming ability and decreasing protein denaturation during frozen storage (Lee 1984;Lanier 1986;Scott et al 1988), and enhances color and flavor of products (Toyoda et al 1992). A substantial amount of muscle proteinases are also removed during the washing process in surimi production (Morrissey et al 1995;Benjakul et al 1998), resulting in less activity in surimi Benjakul et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Highest percent of moisture (88.40) found for the raw muscle of H. neherius and lowest percent was found (approximately 74%) for raw muscle of C. madrasensis. For surimi product of each sample moisture content was found close to approximately 3-12 percent less of the raw muscle which is within the acceptable limit for surimi preparation (Holmquist et al, 1984;Scott et al, 1988). The variation in gel quality due to variation in moisture content level (above or below the said range) was also reported by these authors.…”
Section: Resultsmentioning
confidence: 49%
“…pH and TPC of surimi varied within a narrow range of 6.6-7.06 and 3.7-4.92 log10 cfu/g, respectively, with no significant difference either with sugar mixture concentration or with storage period, indicating absence of any significant chemical or microbial activity during the period of study. Scott et al (1988) also observed that the pH of Alaska pollock surimi varied only slightly between 7.0 and 7.3 and showed no trend of increase or decrease with prolonged storage. According to Jittinanda et al (2005) frozen storage time does not affect psychrotrophic counts of surimi treated with any cryoprotectant.…”
Section: Resultsmentioning
confidence: 81%